#TITLE_ALTERNATIVE# - AHMAD (NIM. 322 93 021); Tim Promotor : Prof. Oei Ban Liang, Ph.D.,; Dr. Jr Tjandra Setiadi, ADRIANTO
One of the impacts of the projected growth of the palm oil industry in Indonesia will be the large amount of wastewater generated from these industries. Therefore, research on palm oil wastewater processing will be one of the issues forced by these industries. This paper describes a research on palm oil wastewater processing, consisting of three sequential phases. The first phase was an effort to identify microorganisms involved in the biodegradation of palm oil wastewater. Results showed that biomass seed collected from an anaerobic baffled bioreactor demonstrates high activity and is capable of degrading organic complex compounds. Bacteria identified in the biomass seed were Clostridium sp2, C. limosum and C. cochlear/um. This seed was then developed for use in the second and third phases of the research. The second phase was an effort to study the kinetics of the anaerobic biodegradation reaction. A fundamental study of hydrolysis reaction kinetics was used as a basis for the development of the anaerobic biodegradation process. Results demonstrated that the hydrolysis process of multi-substrates and single substrates are controlled by oil-tat with a hydrolysis rate constant (kh) of 0,098 day and 0,22 day respectively. Both hydrolysis reaction rates followed the first order reaction kinetics. An inspection of the kinetics showed that the biodegradation process of palm oil wastewater is controlled by the oil-fat compound. This result supports the assumption that oil and fat are more difficult to degrade than carbohydrates and proteins. A model for the biodegradation reaction was then designed based on the study of kinetics of the process. The fundamental study on kinetics of a continuous bioreactor system was adopted as the basis for the development of the anaerobic bioreactor system. The kinetic parameter is an important variable in designing the bioreactor. In particular, the constant rate of maximum growth determines the minimum biomass detention time. The minimum biomass detention time is a critical factor in bioreactor operation for processing palm oil wastewater.